Re-defining the yam (Dioscorea spp.) core collection using morphological traits - Girma Tessema, G.; Bhattacharjee, Ranjana; López Montes, Antonio José; Gueye, B.; Ofodile, S.; Franco, J.; Abberton, Michael T. (Cambridge University Press, 2017)
Development of core collection representing the diversity in the entire germplasm creates a better access and enhanced utilization of the main collection thus allowing rapid evaluation in crop improvement programs. Core collections are dynamic in nature and needs revisiting when additional germplasm and information becomes available. In the current study, an attempt was made to re-define the previously developed yam (Dioscorea spp) core collection using 56 morphological traits. Information on additional acquired germplasm and presence of duplicates or mislabelled accessions in the entire collection was also used. The re-defined core collection consisted of 843 accessions and represented about 20% of the entire collection. It included six Dioscorea species, of which accessions of Dioscorea rotundata are in the majority (73.54%) followed by Dioscorea alata (21.35%), Dioscorea bulbifera (1.66%), Dioscorea cayenensis (1.42%), Dioscorea dumetorum (1.42%) and Dioscorea esculenta (0.59%). The Shannon weaver diversity index and principal component analysis revealed the maximum diversity captured in the core from the base collection. This re-defined core collection is more valuable than the original core since it represents true-to-type accessions ensuring reliability for enhanced utilization of germplasm in yam improvement programs.